The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1021/acs.est.6b03749
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model Development for Aviation Black Carbon Mass Emissions from Alternative and Conventional Fuels at Ground and Cruise

Abstract: The first order approximation (FOA3) currently employed to estimate BC mass emissions underpredicts BC emissions due to inaccuracies in measuring low smoke numbers (SNs) produced by modern high bypass ratio engines. The recently developed Formation and Oxidation (FOX) method removes the need for and hence uncertainty associated with (SNs), instead relying upon engine conditions in order to predict BC mass. Using the true engine operating conditions from proprietary engine cycle data an improved FOX (ImFOX) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…The particle mass concentration at the exit plane can be estimated via different generic models for turboshaft engines. We applied the imFOX model [30] and the FOA3 model [31] to the reference kerosene runs ( Figure SI4).…”
Section: Emission Of Particlesmentioning
confidence: 99%
“…The particle mass concentration at the exit plane can be estimated via different generic models for turboshaft engines. We applied the imFOX model [30] and the FOA3 model [31] to the reference kerosene runs ( Figure SI4).…”
Section: Emission Of Particlesmentioning
confidence: 99%
“…3,4,[7][8][9][10][11] Due to their potential health and climate impacts, various research programs have focused on characterization of particle emissions from aircraft engines, development of measurement techniques and predictive models for estimating aviation nvPM emissions. [12][13][14][15][16][17] Recent research has been motivated also by the development of a certification standard for nvPM emissions of new commercial aircraft turbine engines. [18][19][20][21][22] The International Civil Aviation Organization 55 (ICAO) has adopted the nvPM standard that applies to all engine types rated >26.7 kN thrust in 56 production on or after 1 January 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated LTO mass emission is comparable with the data in AEIC-FOA3 (0.6 Gg) and EDGAR (0.6 Gg) inventories, but significantly smaller than that in AEIC-FOX (2.4 Gg). The recent studies 27,44 indicated that the FOX method might overestimate the BC mass emission by up to a factor of 4. The estimated CCD emission is also in line with the data in EDGAR (8.4 Gg), but the differences are relatively large compared with the AEIC estimations by FOA3 (1.4 Gg) and FOX (14.5 Gg) methods, which is assumed to be caused by the different adopted engine fuel flows at cruise 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the paucity of BC particle emission data in the ICAO (International Civil Aviation Organization) Emission Databank (EDB) 19 , majority of the currently commonly utilized global aviation emission inventories 20–23 only contain gaseous emissions including unburnt hydrocarbons (HC), carbon monoxide (CO) and oxides of nitrogen (NO x ). Many studies tried to correlate the BC mass emission with the current regulatory metric Smoke Number (SN), including the SN dependent First Order Approximation (FOA1.0 to FOA3.0) methods 24,25 , the semi-empirical SN independent Formation OXidation methods FOX 26 and imFOX 27 , and the scaling methods for the cruise emissions 28 . The emergence of these methods led to the developments of BC mass emission inventories, e.g., AERO2k 29 , AEIC 26 , and AEDT 30 .…”
Section: Introductionmentioning
confidence: 99%